GEOCHEMISTRY AND SEDIMENTARY PETROLOGY OF ARCHEAN CLASTIC SEDIMENTARY ROCKS AT MT. GOLDSWORTHY, PILBARA CRATON, WESTERN AUSTRALIA: EVIDENCE FOR THE EARLY EVOLUTION OF CONTINENTAL CRUST AND HYDROTHERMAL ALTERATION - Sugitani K.; Yamashita F.; Nagaoka T.; Yamamoto K.; Mimura K.; Minami M.; Suzuki K. (My University, 2006)
Geochemical and petrological analyses of Archean clastic metasedimentary rocks at Mt. Goldsworthy in the Pilbara Craton, Western Australia reveal the early evolution of continental crust and the Earth's surface environment. The succession correlative to the ca. 3.4 Ga Strelley Pool Chert is composed dominantly of silicified medium-grained to very coarse-grained sandstone, siltstone and shale, with minor chert and precipitative beds of nahcolite and barite. The sandstone is generally rich in detrital quartz, with the coarse-grained sandstone containing abundant, very well rounded mono-crystalline quartz that is assumed to be derived from older sedimentary rocks. The recycled detritus is mixed with first-cycle detrital material such as feldspar and barite that is sourced from reworked precipitative beds. The sandstone also contains zircon, Fe-Ti oxides, sulfides and lithic fragments of various origins including mafic-ultramafic volcanic rocks, sedimentary and possibly metamorphic rocks. Al-Ti-Zr systematics indicates that the source area for the Mt. Goldsworthy clastic metasedimentary rocks was locally subjected to hydrothermal alteration. Reaction with the acid solution resulted in Al-dissolution and the formation of Zr- and Ti-enriched residual detrital material. The enrichment in heavy rare earth elements and low Al2O3/TiO2 values of Mt. Goldsworthy samples reflects the inflow of the residual zircon- and Ti-oxides-enriched detritus. Th/Sc, La/Sc and Eu/Eu* ratios that are unaffected by contamination by the residual detritus indicate a mixed provenance with a significant contribution from granitoid rocks. The presence of detrital zircon older than 3.5 Ga was also demonstrated in this study. © 2006 Elsevier B.V. All rights reserved.
Keywords: ARCHEAN; CRUSTAL EVOLUTION; HYDROTHERMAL ALTERATION; MT. GOLDSWORTHY; PILBARA; TRACE ELEMENT GEOCHEMISTRY; Precambrian::Archean; Докембрий::Архей